Ukraine 2022, through the leadership binoculars. (October 2022) - Sanders, Paul
The essay provides a take, by a historian, on the 2022 Ukraine war. It draws attention to the fact that, over the past 20 years, terms such as "game-changer" or "turning point" have been frequently employed to characterize important junctures. However, 2022 is qualitatively different from all of these, as it represents the antithesis to 1989 and marks the end of an entire era. From the leadership perspective, one immediate effect of a turning point is the reckoning with the past that it entails. It forces a rethink on past behavior. And this collective cognitive rewiring triggers the questioning of the legacy of leaders associated with the now discredited course of action. Taking the example of the crisis of conscience currently underway in Germany, the essay cautions against scapegoating that relies on retrospective selection bias; suggesting instead, that the focus of attention should be shifted to the collective cognitive blinders that prevented the numerous Cassandras, who understood the genuine nature of Putinist aggression, from being listened to. The essay then turns its attention to the proliferation of historical analogies and comparisons, arguing that this tells us less about the event and more about the fact that our compasses have gone haywire. As corollaries of our profound disarray, they even prevent us from gaining a better understanding of the phenomenon. This is addressed in the final part, which includes reflections on Putin as a leader, Putinist followership, as well as the challenges Western leaders are likely to face in the future.